2003
DOI: 10.1179/026708303225002019
|View full text |Cite
|
Sign up to set email alerts
|

Grain refinement and superplastic behaviour of a modified 6061 aluminium alloy

Abstract: The superplastic properties and microstructure evolution of a 0 . 15%Zr and 0 . 7%Cu modi ed 6061 aluminium alloy were examined in tension at temperatures ranging from 475 to 600°C and strain rates ranging from 7610 2 6 to 2 . 8610 2 2 s 2 1 . The re ned microstructure with an average grain size of about 11 mm was produced in thin sheets by a commercially viable thermomechanical process. It was shown that the modi ed 6061 alloy exhibits a moderate superplastic elongation of 580% in the entirely solid state at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…35 Figures 5 and 6 show that the peak η of 6061 aluminium alloy is not >0·42. Furthermore, Kaibyshev et al studied high temperature deformation behaviour of 6061 aluminium alloy and concluded that superplastic deformation occurred at higher deformation temperature than 773 K. 1,2,36,37 Therefore, the superplastic deformation may not appear in this study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…35 Figures 5 and 6 show that the peak η of 6061 aluminium alloy is not >0·42. Furthermore, Kaibyshev et al studied high temperature deformation behaviour of 6061 aluminium alloy and concluded that superplastic deformation occurred at higher deformation temperature than 773 K. 1,2,36,37 Therefore, the superplastic deformation may not appear in this study.…”
Section: Discussionmentioning
confidence: 71%
“…The power law, equation (1), and the exponential law, equation (2), are suitable for low and high stress, respectively. The hyperbolic sine law, equation (3), is a more general form suitable for stresses over a wide range.…”
Section: Mechanical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the closer the material is to the tool head, the higher the temperature and temperature gradient. The maximum temperature of the material 2 mm away from the tool head reaches 433°C, which is 75% of the melting point (575°C) of 6061 aluminium alloy [26]. The maximum temperature is close to the maximum temperature reached by the materials in FSW at a distance of 1.50 mm from the shoulder (450°C) [27].…”
Section: Resultsmentioning
confidence: 99%
“…6082-T6 aluminium alloy is a medium-strength heattreatable Al-Mg-Si alloy with good forging properties, weldability, corrosion resistance, and machining characteristics, which is widely used in the field of highspeed trains and urban rail vehicles [1][2][3][4]. Welding is the main manufacturing method of aluminium alloy connection, and the performance of the joint is closely related to the welding process and composition of the welding materials.…”
Section: Introductionmentioning
confidence: 99%